Iguratimod as an alternative therapy for systemic sclerosis and prevention of the occurrence of ischemic digital ulcer - Yan, Qingran; Liu, Bei; Wang, Jieying; Yin, Hanlin; Li, Qianqian; Lu, Liangjing (Frontiers in Medicine, 2023)
Objectives: To assess the effectiveness of iguratimod (IGU) as an alternative treatment for systemic sclerosis (SSc), especially in prevention of ischemic digital ulcers (DU). Methods: We constructed two cohorts from the Renji SSc registry. In the first cohort, SSc patients receiving IGU were observed prospectively with effectiveness and safety. In the second cohort, we picked up all the DU patients with at least a 3-month follow-up to investigate the prevention of IGU on ischemic DU. Results: From 2017 to 2021, 182 SSc patients were enrolled in our SSc registry. A total of 23 patients received IGU. With a median follow-up of 61 weeks (IQR: 15-82 weeks), the drug persistence was 13/23. 91.3% of the patients (21/23) were disease worsening-free in the last visit with IGU. Ten patients withdrew; 2/10 due to disease worsening, 3/10 due to incompliance, and 5/10 due to mild-to-moderate side effects. All the patients with side effects recovered fully after stopping IGU. Of note, 11 patients had ischemic DU, and 72.7% (8/11) patients had no new occurrence of DU during the follow-up. In the second cohort of 31 DU patients received background vasoactive treatments with a median follow-up of 47 weeks (IQR, 16-107 weeks), IGU treatment was protective of new DU occurrence (adjusted risk ratio = 0.25, 95% CI, 0.05-0.94, adjusted odds ratio = 0.07, 95% CI, 0.01-0.49). Conclusions: Our study indicates IGU as a possible alternative treatment for SSc. Beyond expectation, this study for the first time describes IGU as preventative against ischemic DU occurrence and merits further investigation.